Sistem Informasi Pengiriman Barang Pada PT Citra Abadi Cargo Menggunakan Metode Personal Extreme Programming (PXP) - Bayu Agung Setiawan; Gita Indah Marthasari; Christian Sri Kusuma Aditya (Universitas Muhammadiyah Malang, 2025)
Goods delivery service is a service to service users to deliver both documents and goods to be sent to the intended address. The distribution of goods is usually carried out by companies engaged in transportation, especially in freight forwarding services, one of which is PT Citra Abadi Cargo. At present, PT Citra Abadi Cargo in recording delivery data is still done manually, this results in frequent duplication of data. recording of goods delivery data and making goods delivery reports is one of them. As for the things that make the vulnerability of recording errors by using proof of payment and delivery reports in the form of paper notes. Incomplete recording results in delays in the process of shipping goods. In addition, it is prone to data loss due to delays in recording data on goods to be sent, thus slowing down the process of making reports. The method used in this research is the Personal Extreme Programming (PXP) method. This research aims to build a goods delivery information system that is able to meet the needs of users, especially at PT Citra Abadi Cargo. The results of this study can be concluded based on UAT (User Acceptance Test) testing the system built according to user needs with an average value of 77% which is included in the good category. Estimated system development time for 17 days based on previous planning or planning stages got an additional time in iteration 2 of 7 days. So that the total estimate in working on this system is 22 days.